Modelo para simulação de supercondutor HgRe-1223 para aplicações como limitador de corrente resistivo - Freitas, Tiara Rodrigues Smarssaro de (2009)
The conventional protective devices connected to the electrical system and the equipment connected to it, are generally unable to support the electromechanics efforts from the occurrence of electromechanical faults in the system. The situation became more critical with the expansion of electrical systems, which caused an increase of short-circuit courrent, leading to the development of devices that in the event of a failure, isolate the fault and achieve the proper protection. These devices limit the short-circuit current while the protection systems do not work, isolating the fault, and they are called limiters of fault current (LFC). Additionally, they should not interfere in the normal operation of the system. With the advance of technology of superconducting devices, with increasing temperature of operation, its application as a current limiter has advantages over other existing technologies. This dissertation presents a model for simulation in the time domain of a current limiter superconducting resistive applied to electrical systems. The superconductor current limiter model is obtained from the observation of the resistance variation with the current that flows by the limiter during the transition between superconducting state and normal state. The superconducting behavior is analyzed, resulting in equations that represent its resistive behavior between the transition from superconducting state to normal state and vice versa. The model is simulated in MATLAB/Simulink and ATPDraw; both simulations are detailed and compared with experimental results. The experimental results and the results obtained show the good performance of the model and validate its use in simulations of electrical systems in behavior analysis in the occurrence of transient faults.